Makna frasa sehat jasmani sebagai syarat unuk diangkat sebagai notaris - Anshori, Muhammad Burhanuddin (Jurnal Cakrawala Hukum, 2022)
The problem in this study relates to the meaning of the phrase "healthy body" as a condition to be appointed as a notary according to the rules contained in Article 3 letter d of Law No. 2 of 2014 regarding work opportunities for people with disabilities who are physically healthy and have physical characteristics of people with disabilities a notary candidate who can be appointed as a notary as referred to in the Law on Notary Positions. The results of this study indicate that the meaning of "physically healthy" as a requirement to be appointed as a Notary is explained in Article 3 Letter D of the UUJN. A physically disabled person must have the same opportunity to be appointed as a Notary as other people, but the equality of opportunity must pay attention to his ability to carry out his duties as a Notary in order to maintain the credibility of the Notary Position. A person with disabilities can still be said to be in good health if he can still carry out his obligations as a Notary like a physically disabled person who can speak fluently, and can write or type well because he can still move his hands and fingers well but cannot walk properly because unable to move one part of his leg, then for a physically handicapped person such as these criteria still meet the benchmarks to be appointed as a notary. How to cite item:Â  Anshori, M. (2022). Makna frasa sehat jasmani sebagai syarat unuk diangkat sebagai notaris.Â Jurnal Cakrawala Hukum, 13(1), 10-19. DOI:https://doi.org/10.26905/idjch.v13i1.5183.